Industry 4.0 and Lean Manufacturing, using the MAUT Method - R, Tardio Paulo; Miquele, Nasario; Jones, Schaefer L; OB, Nara Elpidio (Trends in Computer Science and Information Technology, 2024)
Industry 4.0 covers a wide range of areas, such as production processes, efficiency, data management, consumer relationships, and competitiveness. It is also becoming a topic of academic study, with researchers and scholars exploring various questions related to this revolution. Furthermore, the text mentions the Toyota Production System, which promotes efficiency and effective communication in production operations and introduces the concept of Lean Manufacturing, which aims to reduce costs and increase efficiency. The integration of Industry 4.0 with Lean Manufacturing is referred to as “Lean 4.0”. The method used in this article was a questionnaire sent to manufacturing companies in southern Brazil and analyzed the data obtained through the Multi-Attribute Utility Theory (MAUT), which is presented as a decision-making tool that allows comparing alternatives taking into account multiple criteria. The conclusions of this study show that both the views of senior management and those surveyed consider that the companies involved in this research will be in 5 years, with their Industry 4.0 well developed. On the Lean Manufacturing side, considering only the view of those surveyed, they consider that the companies involved in this study will be in 5 years, with Lean Manufacturing quite developed. The practical contribution of this study shows that the companies participating in the study are committed to adopting advanced manufacturing technologies and practices. This conclusion is important because it indicates that companies are aware of the opportunities and challenges of Industry 4.0 and Lean Manufacturing.